2021
DOI: 10.1109/msp.2021.3075932
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography-Based Auditory Attention Decoding: Toward Neurosteered Hearing Devices

Abstract: People suffering from hearing impairment often have difficulties participating in conversations in so-called 'cocktail party' scenarios with multiple people talking simultaneously.Although advanced algorithms exist to suppress background noise in these situations, a hearing device also needs information on which of these speakers the user actually aims to attend to. The correct (attended) speaker can then be enhanced using this information, and all other speakers can be treated as background noise. Recent neur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 38 publications
(105 reference statements)
6
112
1
Order By: Relevance
“…Very recently, convolutional networks have been applied for auditory attention detection [14], [12], [15], [16]. Instead of a two-step approach (reconstructing the attended stimulus and comparing the similarity with the actual stimuli), these convolution-based models can classify the attended speaker directly from the EEG and envelope of the speech signal.…”
mentioning
confidence: 99%
“…Very recently, convolutional networks have been applied for auditory attention detection [14], [12], [15], [16]. Instead of a two-step approach (reconstructing the attended stimulus and comparing the similarity with the actual stimuli), these convolution-based models can classify the attended speaker directly from the EEG and envelope of the speech signal.…”
mentioning
confidence: 99%
“…Cognitively controlled hearing aids have the capacity to improve the listener experience in cluttered environments through listener‐steered speech enhancement (Geirnaert et al, 2021). Understanding endogenous switching may speed attention decoding by identifying the intended attended talker throughout a switch before the new attended talker is fully attended to.…”
Section: Discussionmentioning
confidence: 99%
“…AAD in combination with speaker separation has the potential to be incorporated into cognitively controlled hearing aids to provide auditory enhancement in speech‐rich scenes that traditional hearing aids struggle with (Borgström et al, 2021; Popelka & Moore, 2016). The majority of these studies' protocols ask listeners to sustain attention, not invoking switches in attention (Geirnaert et al, 2021). However, it is critical to study attention switching given the prevalence of switching in real‐world conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Consider a C -channel EEG signal of which the c th channel is denoted by x c ( t ), with t the time sample index. In the linear stimulus reconstruction paradigm, a spatio-temporal filter or decoder d c ( l ) is applied to this C -channel EEG signal to reconstruct the speech envelope of the attended speaker s a ( t ) [5]–[7]: with the channel index c ranging from 1 to C (spatial combination of C channels) and the time lag index l ranging from 0 to L – 1 (temporal integration over L time samples). This filter is an anti-causal filter, as L post-stimulus time lags are used to reconstruct the attended speech envelope from the EEG signal.…”
Section: (Un)supervised Stimulus Reconstruction For Aadmentioning
confidence: 99%
“…It has been extensively shown that the auditory attention information is encoded in brain signals [1]–[3], which can be recorded, for example, using electroencephalography (EEG). As such, EEG-based AAD technology could contribute to so-called ‘neuro-steered’ hearing devices [4], [5].…”
Section: Introductionmentioning
confidence: 99%